Diatomite-based Janus membrane as well as preparation method and application thereof

The diatomaceous earth-based Janus film was prepared by silane-modified diatomaceous earth and polymer composite and oxidation reaction, which solved the problems of complex preparation methods of existing Janus films and poor material performance stability, and achieved efficient separation of oil-water and oil-water emulsions.

CN119746654AActive Publication Date: 2025-04-04CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411943043.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing Janus film preparation methods are complex, the material performance is poor, and it is difficult to effectively solve the problem of water pollution, especially in oil-water separation and oil-water emulsion separation.

Method used

A diatomaceous earth/polymer composite film was prepared by silane-modified diatomaceous earth and polymer composite film, and the hydrophobic thiol group on one side of the film was converted into a hydrophilic sulfonic acid group through oxidation reaction to prepare a diatomaceous earth-based Janus film with hydrophobic and hydrophilic on the other side.

Benefits of technology

It realizes efficient oil-water separation and oil-water emulsion separation, with a separation efficiency of more than 99%, and the material has good physical properties and stability, which is suitable for complex liquid separation tasks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746654A_ABST
    Figure CN119746654A_ABST
Patent Text Reader

Abstract

The invention discloses a diatomite-based Janus film as well as a preparation method and application thereof, relates to the technical field of functional films, and solves the problems of complex preparation method and unstable material performance of the Janus film in the prior art. The preparation method of the diatomite-based Janus membrane comprises the following steps: (1) reacting diatomite, an organic solvent, a catalyst and a silane coupling agent to obtain silane modified diatomite; (2) reacting the modified diatomite with a polymer to prepare a diatomite / polymer solution, and drying to form a film to obtain a diatomite / polymer composite film; and (3) carrying out oxidizing agent steam fumigation treatment on one side of the diatomite / polymer composite membrane to obtain the diatomite / polymer Janus membrane. The porous structure of the silane modified diatomite is utilized, a large number of pore channels can be formed in the membrane, and the application of the Janus membrane in oil-water separation is ensured; through oxidation reaction treatment, the hydrophilic side of the Janus membrane has an underwater oleophobic characteristic, and the hydrophobic side of the Janus membrane has an under-oil hydrophobic characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional films, and in particular to a diatomite-based Janus film and a preparation method and application thereof. Background Art

[0002] At present, water pollution has become one of the major environmental challenges facing the world. With the acceleration of industrialization and urbanization, the sources of water pollution are increasing, including agricultural wastewater, industrial wastewater, domestic sewage and plastic pollution. Water pollution not only seriously harms the ecological environment, but also directly affects human drinking water safety, food safety and life and health. Therefore, the development of water treatment and water pollution control technology has become the focus of current research.

[0003] Membrane separation technology is an efficient, energy-saving and environmentally friendly separation technology. It has made significant progress in many fields such as water treatment, gas separation, food processing, chemical engineering, etc. Among them, Janus membrane is a membrane material with a special structure. It has two surfaces with opposite properties, that is, one side is hydrophilic or hydrophobic, and the other side has the opposite property. There are two existing preparation strategies for Janus membranes. One is to use a physical method to compound two polymer films with different properties, such as the Chinese patent document CN110039863A. This document uses hot pressing and bonding methods to prepare double-sided anisotropic micro-nano composite fiber membranes, and uses centrifugal spinning or electrospinning technology to prepare hydrophilic CA fiber membranes and hydrophobic PVDF fiber membranes. The PVDF fiber membrane has super-hydrophobic properties by coating SiO2 and plasma grafting treatment technology. The hydrophilic CA fiber is bonded under hot pressing (90-130°C) or dopamine and polyurethane bonding conditions. The single-sided super-hydrophobic and single-sided hydrophilic Janus micro-nano fiber membrane is laminated with a super-hydrophobic PVDF fiber membrane. Although this method can be used for oil-water separation, its preparation method is complicated, the separation efficiency needs to be improved, and it does not have the ability to separate oil-water emulsions. Chinese patent document CN113774559A provides a PU (CA / PU) CA nanofiber Janus membrane with CA / PU blended nanofibers as a transition interlayer. The application of the transition interlayer improves the thermal stability and interfacial compatibility of the membrane to a certain extent, but there are problems of insufficient membrane stratification and low uniformity. Another strategy is to modify the wettability of both sides or one side of the film differently, such as the Chinese patent document CN111871001A. The document first immerses the substrate in an aqueous solution containing acidic organic matter and water-soluble iron salts for modification to make it super hydrophilic. Under the protection of water, one side of the substrate is modified with polydimethylsiloxane, so that the prepared Janus material has one side super hydrophilic and the other side super hydrophobic, showing asymmetric wettability, and can achieve directional water transport in air or oil. However, the Janus membrane prepared by this method is not easy to control and the performance stability of the material is poor.

[0004] Therefore, in order to solve the above problems, the researchers tried to combine the two strategies, explore new composite materials and advanced preparation processes, and develop a double-sided asymmetric wetting Janus composite membrane that is hydrophobic on one side and hydrophilic on the other side. Summary of the invention

[0005] In order to solve the problems of complicated preparation methods and poor stability of material performance of the prior art Janus membrane, the present invention proposes a diatomite-based Janus membrane and its preparation method and application. The technical solution of the present invention is as follows:

[0006] A method for preparing a diatomite-based Janus membrane comprises the following steps:

[0007] S1: Weigh diatomaceous earth, an organic solvent, a catalyst, and a silane coupling agent, add them into a reactor for reaction, and after the reaction is completed, filter, wash, and filter again the reaction solution to obtain silane-modified diatomaceous earth;

[0008] S2: Weighing a polymer, a surfactant, a dispersant, and a solvent, adding them to a reactor, stirring to form a uniform polymer solution, continuing to add the silane-modified diatomaceous earth prepared in S1, stirring to obtain a uniform diatomaceous earth / polymer solution, coating the diatomaceous earth / polymer solution on a coating machine into a thin film, immersing the thin film in a precipitant and allowing it to stand, and drying to obtain a diatomaceous earth / polymer composite film;

[0009] S3: fumigating one side of the diatomite / polymer composite membrane prepared in S2 with oxidant steam to obtain a diatomite / polymer Janus membrane;

[0010] Further, the organic solvent is one or a combination of at least two of toluene, xylene, cyclohexane and cyclohexanone;

[0011] Further, the catalyst is one or a combination of at least two of N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, triethylamine and N,N-dimethylbenzylamine;

[0012] Further, the silane coupling agent is one or a combination of at least two of 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane;

[0013] Furthermore, the polymer is polylactic acid (PLA), polybutylene adipate / terephthalate Diesters One or a combination of at least two of (PBAT), polyester elastomer (TPEE), nylon, nylon elastomer, ethylene-vinyl acetate copolymer (EVA), polyurethane elastomer, polysulfone, polyethersulfone and polyacrylonitrile;

[0014] Further, the surfactant is one or a combination of at least two of cetyltrimethylammonium bromide (CTAB), sodium dodecylbenzene sulfonate (SDBS), polysorbate (Tween) and sorbitan fatty acid (Span);

[0015] Further, the dispersant is one or a combination of at least two of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol;

[0016] Further, the solvent is one or a combination of at least two of chloroform, tetrahydrofuran, dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and hexafluoroisopropanol;

[0017] Further, the precipitant is any one of water, ethanol, a water-dimethylformamide mixture, a water-dimethyl sulfoxide mixture, an ethanol-tetrahydrofuran mixture, and an ethanol-chloroform mixture;

[0018] Furthermore, the oxidant is one or a combination of hydrogen peroxide and peracetic acid;

[0019] Furthermore, the diatomite-based Janus membrane has an asymmetric porous structure on both sides, one side is a hydrophobic layer, and the other side is a hydrophilic layer, and the thickness thereof is 5 to 500 μm;

[0020] Furthermore, the reaction temperature in S1 is 60° C. and the reaction time is 6 h;

[0021] Further, the drying temperature in S2 is 50°C;

[0022] Further, the heating temperature in S3 is 80° C.;

[0023] Furthermore, the diatomaceous earth particle size is 5 to 50 μm;

[0024] Furthermore, the specific surface area of ​​the diatomite is greater than or equal to 30m 2 g -1 ;

[0025] Furthermore, the mass ratio of the diatomaceous earth to the silane coupling agent is 1 to 20:1;

[0026] Furthermore, the mass ratio of the polymer, surfactant, dispersant and diatomaceous earth is 1-20:0.05-0.5:0.01-1:1.

[0027] A diatomite-based Janus membrane is prepared by applying the preparation method.

[0028] An application of the diatomite-based Janus membrane is applied to oil-water separation.

[0029] Compared with the prior art, the present invention solves the problems of complicated Janus membrane preparation process and poor material performance stability in the prior art, and has the following specific beneficial effects:

[0030] 1. The present invention prepares a polymer / diatomite composite membrane by compounding silane-modified diatomite with a polymer. Since the thiol-modified diatomite is hydrophobic, the prepared diatomite / polymer composite membrane is hydrophobic. The hydrophobic thiol group on one side of the diatomite / polymer composite membrane is converted into a hydrophilic sulfonic acid group through an oxidation reaction, so that the polymer / diatomite composite membrane is changed from being hydrophobic on both sides to being a diatomite-based Janus membrane with asymmetric wetting on both sides, with one side being hydrophobic and the other side being hydrophilic. The hydrophilic side of the diatomite-based Janus membrane has the property of being oleophobic underwater, while the hydrophobic side has the property of being hydrophobic under oil.

[0031] 2. Since the silane-modified diatomite has a porous structure of nanometer and micrometer sizes and is evenly dispersed inside the Janus membrane, a large number of pore channels are formed in the diatomite-based Janus membrane. The presence of these pores ensures that the diatomite-based Janus membrane can achieve efficient screening and filtering in oil-water separation, and is particularly suitable for treating oily wastewater, oil-water emulsions and other liquids with high viscosity and complex components. It can also reduce membrane pollution and blockage problems that may occur during the separation process, thereby achieving more efficient and economical oil-water separation. The diatomite-based Janus membrane prepared by the present invention has an efficiency of oil-water separation and oil-water emulsion separation of more than 99%.

[0032] 3. Since diatomite itself has excellent chemical corrosion resistance, thermal stability and high temperature resistance, the present invention uses silane-modified diatomite as the base material, which not only enhances the structural stability of the diatomite-based Janus membrane in terms of microstructure, but also significantly improves the overall physical properties of the diatomite-based Janus membrane, so that the diatomite-based Janus membrane can effectively cope with complex separation tasks for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a characterization diagram of the water contact angle of the hydrophilic side of the diatomaceous earth / polysulfone composite Janus membrane prepared in Example 1;

[0034] Figure 2 This is a characterization diagram of the water contact angle of the hydrophobic side of the diatomaceous earth / polysulfone composite Janus membrane prepared in Example 1;

[0035] Figure 3 It is a schematic diagram of an oil-water separation device;

[0036] Figure 4 This is a characterization diagram of the underwater chloroform contact angle of the hydrophilic side of the diatomaceous earth / polysulfone composite Janus membrane prepared in Example 1. DETAILED DESCRIPTION

[0037] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0038] Example 1.

[0039] S1: 50 g of diatomaceous earth with a particle size of 20 μm, 500 g of toluene, 0.5 g of triethylamine and 5 g of 3-mercaptopropylmethyldimethoxysilane were weighed and added into a reactor, and reacted at 60° C. for 6 h. After the reaction, the reaction solution was filtered, washed with ethanol, filtered again, and then dried at 60° C. to obtain 51.8 g of silane-modified diatomaceous earth;

[0040] S2: 50 g of polysulfone, 0.2 g of Span 80, 2 g of polyvinyl pyrrolidone and 400 g of DMF were weighed and added into the reactor, stirred and dissolved, and 5 g of silane-modified diatomaceous earth prepared in S1 was continuously added, and mechanical stirring was performed at 60° C. for 2 h, and the stirring speed was 200 rpm to obtain a uniform diatomaceous earth / polymer solution; 10 g of diatomaceous earth / polymer solution was weighed and applied on a coating machine to form a film with a thickness of 100 μm, and the film was immersed in water and allowed to stand for 10 min, and then dried at 50° C. to obtain a diatomaceous earth / polysulfone composite membrane with a thickness of 96 μm;

[0041] S3: Add hydrogen peroxide to the fumigation device, heat it to 80°C to vaporize it, and perform hydrogen peroxide vapor fumigation treatment on one side of the diatomite / polymer composite membrane for 10 minutes to convert part or all of the thiol groups on its surface into sulfonic acid groups, thereby preparing a diatomite / polysulfone composite Janus membrane. The side treated with hydrogen peroxide vapor fumigation is the hydrophilic side, such as Figure 1 The water contact angle characterization diagram of the hydrophilic side of the diatomite / polysulfone composite Janus membrane shows that the contact angle of the hydrophilic side is 52°; Figure 2 This is a characterization diagram of the water contact angle of the hydrophobic side of the diatomaceous earth / polysulfone composite Janus membrane, and the hydrophobic side contact angle is 126°.

[0042] Example 2.

[0043] S1: 50 g of diatomaceous earth with a particle size of 10 μm, 500 g of toluene, 0.5 g of triethylamine and 8 g of 3-mercaptopropylmethyldimethoxysilane were weighed and added into a reactor, and reacted at 60° C. for 6 h. After the reaction, the reaction solution was filtered, washed with ethanol, filtered again, and then dried at 60° C. to obtain 51.8 g of silane-modified diatomaceous earth;

[0044] S2: 40g PLA, 10g PBAT, 2g polyethylene glycol 400 and 400g chloroform were weighed and added into the reactor, stirred and dissolved, and 10g silane-modified diatomaceous earth prepared in S1 was continuously added, and mechanical stirring was performed at 60°C for 2h, and the stirring speed was 200rpm to obtain a uniform diatomaceous earth / polymer solution; 10g diatomaceous earth / polymer solution was weighed and scraped on a coating machine to form a film with a thickness of 100μm, and the film was immersed in an ethanol-chloroform mixture and allowed to stand for 10min, wherein the mass ratio of ethanol to chloroform was 8:2, and then dried at 50°C to obtain a diatomaceous earth / PLA / PBAT composite film with a thickness of 96μm;

[0045] S3: Add hydrogen peroxide to the fumigation device, heat it to 80°C to vaporize it, and perform hydrogen peroxide vapor fumigation treatment on one side of the diatomite / polymer composite membrane for 10 minutes to convert part or all of the thiol groups on its surface into sulfonic acid groups, thereby preparing a diatomite / PLA / PBAT composite Janus membrane. The side treated with hydrogen peroxide vapor fumigation is the hydrophilic side, and its contact angle is 40°; the other side is the hydrophobic side, and its contact angle is 131°.

[0046] Example 3.

[0047] S1: 50 g of diatomaceous earth with a particle size of 40 μm, 500 g of toluene, 0.5 g of triethylamine and 20 g of 3-mercaptopropylmethyldimethoxysilane were weighed and added into a reactor, and reacted at 60° C. for 6 h. After the reaction, the reaction solution was filtered, washed with ethanol, filtered again, and then dried at 60° C. to obtain 51.8 g of silane-modified diatomaceous earth;

[0048] S2: Weigh 50g of nylon elastomer ( 4012), 0.2g Span 80, 2g polyvinyl pyrrolidone and 400g chloroform are added into the reactor, stirred to dissolve, and then 20g silane-modified diatomite prepared by S1 is added, and mechanical stirring is carried out at 60°C for 2h, and the stirring speed is 200rpm to obtain a uniform diatomite / polymer solution; 10g diatomite / polymer solution is weighed and scraped on a coating machine to form a film with a thickness of 100μm, and the film is immersed in an ethanol-chloroform mixture and allowed to stand for 10min, wherein the mass ratio of ethanol to chloroform is 8:2, and then it is dried at 50°C to obtain a diatomite / nylon elastomer composite film with a thickness of 96μm;

[0049] S3: Add hydrogen peroxide to the fumigation device, heat it to 80°C to vaporize it, and perform hydrogen peroxide vapor fumigation treatment on one side of the diatomite / polymer composite membrane for 10 minutes to convert part or all of the thiol groups on its surface into sulfonic acid groups, thereby preparing a diatomite / nylon elastomer composite Janus membrane. The side treated with hydrogen peroxide vapor fumigation is the hydrophilic side, and its contact angle is 38°; the other side is the hydrophobic side, and its contact angle is 136°.

[0050] Example 4.

[0051] S1: 50 g of diatomaceous earth with a particle size of 20 μm, 500 g of toluene, 0.5 g of triethylamine and 25 g of 3-mercaptopropylmethyldimethoxysilane were weighed and added into a reactor, and reacted at 60° C. for 6 h. After the reaction, the reaction solution was filtered, washed with ethanol, filtered again, and then dried at 60° C. to obtain 51.8 g of silane-modified diatomaceous earth;

[0052] S2: 50 g of polyurethane elastomer (2392ARE), 0.3 g of Tween 60, 5 g of polyethylene glycol 200 and 400 g of chloroform were weighed and added into the reactor, stirred and dissolved, and then 20 g of silane-modified diatomaceous earth prepared in S1 was added, and mechanical stirring was performed at 60°C for 2 h, and the stirring speed was 200 rpm to obtain a uniform diatomaceous earth / polymer solution; 10 g of diatomaceous earth / polymer solution was weighed and scraped on a coating machine to form a film with a thickness of 100 μm, and the film was immersed in an ethanol-chloroform mixture and allowed to stand for 10 min, wherein the mass ratio of ethanol to chloroform was 8:2, and then dried at 50°C to obtain a diatomaceous earth / polyurethane elastomer composite film with a thickness of 96 μm;

[0053] S3: Add hydrogen peroxide to the fumigation device, heat it to 80°C to vaporize it, and perform hydrogen peroxide vapor fumigation treatment on one side of the diatomite / polymer composite membrane for 30 minutes to convert part or all of the thiol groups on its surface into sulfonic acid groups, thereby preparing a diatomite / polyurethane elastomer composite Janus membrane. The side treated with hydrogen peroxide vapor fumigation is the hydrophilic side, and its contact angle is 21°; the other side is the hydrophobic side, and its contact angle is 140°. The following table shows the water contact angles of the Janus membranes prepared in Examples 1-4:

[0054] Hydrophilic side contact angle Hydrophobic side contact angle Example 1 52° 126° Example 2 40° 131° Example 3 38° 136° Example 4 21° 140°

[0055] Oil-water separation test:

[0056] (1) The diatomite / polysulfone composite Janus membrane prepared in Example 1 was placed in a Figure 3White oil and deionized water are mixed into an oil-water mixture at a volume ratio of 20:80 between the two glass containers in the separation device shown, and poured into the separation device for oil-water separation using the hydrophilic side of the Janus membrane. The separation efficiency is calculated by chromatographic analysis. The experimental results show that the separation efficiency of the oil-water mixture reaches 99.92%.

[0057] The separation efficiency in the oil-water separation test can be calculated according to the formula shown in formula (1);

[0058] Separation efficiency (%) = (1-Cp / C0) × 100% (1);

[0059] Wherein, C0 (mg / mL) is the oil content before separation; Cp (mg / mL) is the oil content in the filtrate after separation.

[0060] (2) Add 3.8% by weight of a mixed surfactant of Tween 20 and Tween 80 to a mixture of white oil and deionized water in a volume ratio of 10:90, and emulsify to prepare an oil-in-water emulsion. Figure 3 The oil-in-water emulsion is poured into the glassware between the two glassware in the separation device shown in FIG. Figure 3 In the device shown, the hydrophilic side of the Janus membrane is used to separate the oil-water emulsion. The separation efficiency is calculated by chromatographic analysis. The experimental results show that the separation efficiency of the oil-water emulsion reaches 99.65%.

[0061] (3) The diatomite / polysulfone composite Janus membrane prepared in Example 1 was placed in Figure 3 Chloroform and deionized water were mixed into an oil-water mixture at a volume ratio of 80:20 between the two glass containers in the separation device shown in FIG. Figure 3 The device shown uses the hydrophobic side of the Janus membrane to separate oil and water. The separation efficiency is calculated by chromatographic analysis. The experimental results show that the separation efficiency of the oil-water mixture reaches 99.91%. Figure 4 This is a characterization diagram of the contact angle of chloroform underwater on the hydrophilic side of the diatomaceous earth / polysulfone composite Janus membrane, and the contact angle is 153°.

[0062] (4) Add 3.8% by weight of a mixed surfactant of Span 20 and Span 80 to a mixture of chloroform and deionized water in a volume ratio of 90:10, and emulsify to prepare an oil-in-water emulsion. Figure 3 The water-in-oil emulsion is poured into the separation device shown in FIG. Figure 3In the device shown, the hydrophobic side of the Janus membrane is used to separate the oil-water emulsion. The separation efficiency is calculated by chromatographic analysis. The experimental results show that the separation efficiency of the oil-water emulsion reaches 99.74%.

[0063] In summary, the present invention prepares a polymer / diatomite composite membrane by compounding silane-modified diatomite with a polymer, and further converts the hydrophobic thiol group on one side of the diatomite / polymer composite membrane into a hydrophilic sulfonic acid group through an oxidation reaction, thereby changing the polymer / diatomite composite membrane from being hydrophobic on both sides to being a diatomite-based Janus membrane with asymmetric wetting on both sides, with one side being hydrophobic and the other side being hydrophilic. The nano-scale and micro-scale porous structure of the silane-modified diatomite is utilized to form a large number of pore channels in the diatomite-based Janus membrane, further ensuring that the diatomite-based Janus membrane achieves efficient screening and filtering in oil-water separation, thereby achieving more efficient and economical oil-water separation.

[0064] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.

Claims

1. A method for preparing a diatomite-based Janus membrane, characterized in that: The following steps are involved: S1: Weigh diatomaceous earth, an organic solvent, a catalyst, and a silane coupling agent, add them into a reactor for reaction, and after the reaction is completed, filter, wash, and filter again the reaction solution to obtain silane-modified diatomaceous earth; S2: Weighing a polymer, a surfactant, a dispersant, and a solvent, adding them to a reactor, stirring to form a uniform polymer solution, continuing to add the silane-modified diatomaceous earth prepared in S1, stirring to obtain a uniform diatomaceous earth / polymer solution, coating the diatomaceous earth / polymer solution on a coating machine into a thin film, immersing the thin film in a precipitant and allowing it to stand, and drying to obtain a diatomaceous earth / polymer composite film; S3: fumigating one side of the diatomite / polymer composite membrane prepared in S2 with oxidant steam to obtain a diatomite / polymer Janus membrane; The organic solvent is one or a combination of at least two of toluene, xylene, cyclohexane and cyclohexanone; The catalyst is one or a combination of at least two of N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, triethylamine and N,N-dimethylbenzylamine; The silane coupling agent is one or a combination of at least two of 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; The polymer is polylactic acid, poly(adipate / butylene terephthalate) Diesters , polyester elastomer, nylon, nylon elastomer, ethylene-vinyl acetate copolymer, polyurethane elastomer, polysulfone, polyethersulfone and polyacrylonitrile, or a combination of at least two thereof; The surfactant is one or a combination of at least two of cetyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, polysorbate and sorbitan fatty acid; The dispersant is one or a combination of at least two of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol; The solvent is one or a combination of at least two of chloroform, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide and hexafluoroisopropanol; The precipitant is any one of water, ethanol, a water-dimethylformamide mixture, a water-dimethyl sulfoxide mixture, an ethanol-tetrahydrofuran mixture, and an ethanol-chloroform mixture; The oxidant is one or a combination of hydrogen peroxide and peracetic acid.

2. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The thickness of the diatomite-based Janus membrane is 5 to 500 μm.

3. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The reaction temperature in S1 is 60° C. and the reaction time is 6 h.

4. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The drying temperature in S2 is 50°C.

5. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The heating temperature in S3 is 80°C.

6. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The diatomite particle size is 5 to 50 μm, and the specific surface area of ​​the diatomite is greater than or equal to 30 m 2 g -1 .

7. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The mass ratio of the diatomaceous earth to the silane coupling agent is 1 to 20:

1.

8. The method for preparing a diatomite-based Janus membrane according to claim 1, characterized in that: The mass ratio of the polymer, the surfactant, the dispersant and the diatomaceous earth is 1-20:0.05-0.5:0.01-1:

1.

9. A diatomite-based Janus membrane, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. A use of the diatomite-based Janus membrane according to claim 9, characterized in that: Used in oil-water separation.

Citation Information

Patent Citations

  • Single-side superhydrophobic and single-side hydrophilic Janus type micro-nano composite fiber film and preparation method thereof

    CN110039863A

  • Janus type material with one-way water transport property as well as preparation method and application of Janus type material

    CN111871001A

  • Janus membrane and preparation method thereof

    CN113774559A

  • Method for preparing polyvinylidene fluoride membrane based on sewage treatment

    CN106861463A

  • Diatomite-based filter paper as well as preparation method and application thereof

    CN112553963A